2009
DOI: 10.1016/j.topol.2008.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Heegaard splittings of twisted torus knots

Abstract: Little is known on the classification of Heegaard splittings for hyperbolic 3-manifolds. Although Kobayashi gave a complete classification of Heegaard splittings for the exteriors of 2-bridge knots, our knowledge of other classes is extremely limited. In particular, there are very few hyperbolic manifolds that are known to have a unique minimal genus splitting.Here we demonstrate that an infinite class of hyperbolic knot exteriors, namely exteriors of certain "twisted torus knots" originally studied by Morimot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Applying the bound of Proposition 5.2 to these knots, we see that they have arbitrarily large genus one bridge number. We use the argument of Proposition 4.3 from [20] to show that these knots are hyperbolic: Because K n is primitive on at least one side of Σ, it is a tunnel number one knot. Toroidal tunnel one knots are classified by Morimoto and Sakuma [22] and have genus one bridge number one.…”
Section: Now We Examine Special Cases Of Twisted Torus Knotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the bound of Proposition 5.2 to these knots, we see that they have arbitrarily large genus one bridge number. We use the argument of Proposition 4.3 from [20] to show that these knots are hyperbolic: Because K n is primitive on at least one side of Σ, it is a tunnel number one knot. Toroidal tunnel one knots are classified by Morimoto and Sakuma [22] and have genus one bridge number one.…”
Section: Now We Examine Special Cases Of Twisted Torus Knotsmentioning
confidence: 99%
“…Lee [19] has characterized twisted torus knots which are actually the unknot. Moriah and Sedgwick have shown that certain hyperbolic twisted torus knots have minimal genus Heegaard splittings which are unique up to isotopy [20]. It is also known that twisted torus knots have arbitrarily large volume [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moriah and Sedgwick [12] have asked whether there is a closed 3-manifold with a weakly reducible Heegaard splitting of nonminimal genus. In these examples, both Heegaard splittings are weakly reducible.…”
Section: Introductionmentioning
confidence: 99%
“…So jq = 1 (mod p) and we can see that j > k from (1). Adding equations, we get −(j − k)q = 1 (mod p) and this contradicts equations (2).…”
Section: Introductionmentioning
confidence: 90%